Analisis Parasitologis Telur Nematoda Usus Pada Feses Anak Sekolah Dasar - Hukom, Evi Hudriyah; Junaiddin; Hasnawati (Jurnal Keperawatan Komplementer Holistic, 2025)
Intestinal Nematoda Parasite are worms that inhabit the intestines and can cause digestive disturbances, including malabsorption, which may lead to malnutrition. In 2019, infections caused by these parasites affected approximately 1.5 million people worldwide. This study aims to determine the presence of intestinal nematode eggs in stool samples of elementary school children. This research is a descriptive quantitative study with a cross-sectional approach. The sample consisted of 30 respondent which selected using purposive sampling. The study was conducted as Kristen Kairos 1 Elementary School Sorong City.The results showed that 7 out of 30 samples (23,3%) were found to contain different species of intestinal nematodes, 4 samples (13,3%) were identified as Ascaris lumbricoides, 1 sample (3,3%) as Trichuris trichiura and 2 samples (6,7%) contained both Ascaris lumbricoides dan Trichuris trichiura. The conclusion of this study is that cases of intestinal worm infections are still present among elementary school children. Therefore, preventive efforts are essential. It is recommended that parents and teachers administer deworming medication every six months and provide education on the importance of personal hygene and environmental sanitation to protect children from worm infection.